المصلحة المعتبرة في صياغة القواعد المنظمة للتحقيق الابتدائي - خلف نور الهدى جميل (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The valid interest is a fundamental element in establishing the procedural rules governing the preliminary investigation, which is one of the most important criminal procedures, due to its profound impact on protecting individual rights and ensuring the proper administration of justice. There are controls that the legislator must take into account when formulating the rules governing the preliminary investigation, such that the most deserving interest is given priority. In other words, the more important interest is given priority over the less important interest. This is because there is a conflict between two interests that must be reconciled. The first is the interest of society in quickly uncovering the truth in order to impose punishment on the perpetrator of the crime, and the second is the individual’s interest in protecting their rights and freedoms, which deserve protection from any infringement. Accordingly, the valid interest is not an abstract concept; rather, it is a tool for achieving a balance between protecting individual freedoms and achieving the public interest, represented by achieving criminal justice. Any disruption of this balance may lead to the invalidation of the procedures or compromise the legitimacy of the investigation. This research is based on a basic question: What is meant by the valid interest, and what is its effect or effectiveness in formulating the rules regulating the preliminary investigation, which required us to study the concept of the valid interest, in terms of its definition, conditions and elements, then we moved on to analyse the manner in which this interest is taken into account in formulating the rules of the preliminary investigation, and due to the importance of the method and form of the preliminary investigation in achieving a balance between the private and public interest, we limited the scope of the research from the objective point of view to these two topics.